The Possibility of Asking about Dao: On the Philosophical Significance of Dialogue in the Zhuangzi - Wang, Yiming (Religions, 2023)
In contrast to the aphoristic style of the Daodejing, Zhuangzi is known for its abundant use of dialogues. These dialogues, especially those found in chapters 21 and 22, are consciously organized around the theme of “asking about Dao”. They bring together the diverse propositions about the Dao that are found independently throughout the Daodejing. The purpose of this paper is to highlight the fact that Zhuangzi consciously orders these propositions in terms of the different levels of knowledge of Dao. Within this theoretical framework, Zhuangzi further ranks the questions and answers regarding these propositions. Certain dialogues are partly dismissed because both participants demonstrate a flawed and shallow understanding of the Dao, while other questions and answers are acknowledged and appreciated for their correct and profound understanding of it. There is a strict corresponding relationship between levels of knowledge of Dao and different attitudes toward dialogues in it. Therefore, the examination of the dialogues about the Dao reveals that Zhuangzi places explicit emphasis on the knowledge of the Dao compared to the Daodejing, which also sheds light on Zhuangzi’s distinctive awareness of the problems surrounding this key concept.